Effect of chocolate in migraine: a double-blind study. Issue 4 (April 1974) - Moffett, A. M.; Swash, M.; Scott, D. F.
Abstract : The effect of chocolate on a group of volunteer migrainous subjects, who had observed that headache regularly occurred after the ingestion of small amounts of cocoa products, was investigated. Two separate studies were carried out in a double-blind placebo controlled manner. Only 13 headaches occurred to chocolate alone in 80 subject sessions, and only two subjects responded consistently to chocolate in the two studies. This suggests that chocolate on its own is rarely a precipitant of migraine. Other possible implications of the results are also discussed.